Art Therapy for Chronic Pain: Applications and Future Directions - Angheluta, Anne-Marie; Lee, Bonnie K. (Canadian Journal of Counselling and Psychotherapy, 2011)
Chronic pain is acknowledged as a phenomenological experience resulting from biological, psychological, and social interactions. Consequently, treatment for this complex and debilitating health phenomenon is often approached from multidisciplinary and biopsychosocial perspectives. One approach to treating chronic pain involves implementing mind-body treatments such as art therapy. Art therapy for chronic pain is a nascent area of study, and this literature review endeavours to (a) evaluate the quality of literature investigating this area, (b) discuss how art therapy and other creative arts therapies treated the biopsychosocial dimensions of chronic pain, and (c) identify challenges and future directions for research on this topic.